Proyecto de guardería infantil con aplicación de criterios de arquitectura ancestral en la parroquia Manglaralto - Desiderio Vega, Darling Emanuel (2024)
The following project for a day care center in the Manglaralto parish seeks to establish an educational infrastructure for the care and complementary learning for 60 people, applying ancestral architectural criteria that adhere to the environmental context and cultural heritage of the area. The building will be erected using local and traditional materials and construction techniques, such as bamboo and mud, which are not only sustainable and energy efficient, but also preserve these construction methods to enhance the economy of the sector and the users of the region. On the other hand, the architectural design has open recreational spaces, tiled roofs and louvers, facilitating the circulation of natural air and sunlight, which creates a harmonious and comfortable area for the comfort of infants. Therefore, the project seeks to care for the integrity, safety, and well – being of the infants, as well as to strengthen the identity and cultural personality of the parish by implementing fundamental architectural and aesthetic components that show its ancestral roots. On the other hand, the nursery will not only be an environment to union and conservation between the past and the future where these different techniques are connected and a building is created. Additionally, this approach ensures that the design covers the needs of the people of the sector and contemplates the cultural strengthening of Manglaralto.